The Use of Video as Teaching Media to Improve SMPN 1 Wonosalam Student Understanding on The Topic of Simple Machine - Millah, Isna Lukluil; Ellianawati, Ellianawati (Physics Communication, 2020)
The purpose of this research is to investigate the understanding of physics concept on the topic of simple machine through the application of learning media assisted discovery model. This pre- experimental study used pre-test – post-test. The sample of the research is the students of class VIIIG SMP Negeri 1 Wonosalam Demak academic year 2019/2020. The concept comprehension test results were analyzed using the n-gain test of the mean score and interview questionnaire. The average value of pretest 54 and the average post-test score increased to 87. The gain test results showed the high category. It was concluded that discovery-assisted learning model of video media teaching materials improved the student’s understanding of the concept of simple machine topic.